Mercury exposure modulates antioxidant enzymes in gill tissue and hemocytes of Venerupis philippinarum - X Chen (Invertebrate Survival Journal, 2014)
Mercury (Hg), one of the most hazardous and persistent contaminants, is widespread in the aquatic environment. To establish an effective Hg monitoring strategy, the mRNA expression profiles of four antioxidant enzymes, as well as SOD enzymatic activities and MDA content were investigated at two sublethal HgCl2 exposure doses of 5 and 50 μg L-1 in Venerupis philippinarum gill tissue and hemocytes at 1, 2, 4 and 5 days. All parameters tested showed significant differences between the experimental and control groups at the various time points with tissue-specific manners. GST displayed a dose-dependent increase expression profiles in the two examined tissues. Also decrease expression patterns were detected in Trx and CYP414A1 in both gill and haemocytes with a significant positive relationship of 0.915 in the form tissue (p < 0.01). A positive relationship was found in those of SOD expression and the SOD enzymatic activities in hemocytes (0.683, p < 0.05). Taken together, we found that gill tissue is more suitable for biomarker identification compared to that of hemocytes because of lower variation. This study provides new evidences that mRNA expression of Trx, CYP414A1 and GST in gill tissue has a strong potential as a biomarker for marine mercury monitoring.